Co-expression of p53 and Ki67 and lack of EBV expression in oral squamous cell carcinoma - Iamaroon A. (2014)
BACKGROUND: The objectives of the study were to determine the association between Epstein-Barr virus (EBV) and oral squamous cell carcinoma (OSCC), to compare the expression of p53 and Ki67 between normal oral mucosa, oral hyperkeratosis, oral pre-malignant dysplasia, and OSCC, and to determine the correlation between the expression of p53 and Ki67 in OSCC. METHODS: The expression of EBV mRNA was studied by in situ hybridization technique in 24 cases of OSCC, and the expression of p53 and Ki67 was investigated by immunohistochemical method in 19 cases of OSCC, 7 cases of oral pre-malignant dysplasia, 6 cases of oral hyperkeratosis, and 5 cases of normal oral epithelium. RESULTS: None of OSCC cases expressed EBV-encoded RNA (EBER) transcripts. The labeling indices (LI) of p53- and Ki67-positive cells were significantly higher in OSCC than in oral pre-malignant dysplasia, oral hyperkeratosis, and normal oral mucosa (P < 0.05). A significant correlation between the LI of p53- and Ki67-positive cells was observed in OSCC (r = 0.6; P = 0.01). CONCLUSIONS: These findings suggested that the coexpression of p53 and Ki67 may play roles in carcinogenesis of OSCC and p53 overexpression may promote cell proliferation in OSCC. Furthermore, EBV does not appear to be a risk factor for OSCC particularly in the population of northern Thailand.